Study on the Instability Mechanism and Grouting Reinforcement Repair of Large-Scale Underground Stopes - Chengyu Xie; Nan Jia; Liwen He (Advances in Civil Engineering)
The environmental conditions due to unreasonable mining in underground stopes, the slurry diffusion mechanism in the grouting reinforcement of a stope within its influence, the causes of large-scale instability collapse, and the catastrophic stope process are analyzed, and limit upper line analysis theory and numerical analysis methods are comprehensively adopted, revealing the continuous catastrophic collapse mode of large-scale underground stopes. The method of determining the stope instability collapse boundary and the slip surface within the range based on the theory of the maximum shear strain increment is proposed, and the diffusion radius and range of the grouting slurry during the reinforcement process, which considers the multifield coupling factors, are obtained. The results show that the U-shaped hidden danger area formed after the collapse of the large-scale underground stope. The influence range reaches six adjacent stopes, which are symmetrically distributed around the collapse; the mining instability is manifested as a catastrophic chain process of stress change, energy accumulation, state change, and instability collapse. The damage mode of instability collapse is a combination method of wedge collapse, circular arc rotation, triangular translation, and strip slip. According to the multiphysics coupling numerical calculation, the diffusion radius of the grouting slurry is 12 m, exhibiting an elliptical distribution. The research results can be used to comprehensively control the underground mining environment, thus effectively solving the safety problems faced by tunnel or roadway excavations above the goaf.